2019
DOI: 10.1097/ajp.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spinal Cord and Peripheral Nerve Stimulation Reflected in Sensory Profiles and Endogenous Pain Modulation

Abstract: Objectives: Spinal cord and peripheral nerve stimulation (SCS/PNS) may alleviate chronic pain; however, the underlying mechanisms remain controversial. The aim of this observational study was to assess sensory changes in the ON-conditions and OFF-conditions to obtain insights into the mechanism of analgesic effects of SCS/PNS. Materials and Methods: We contacted 85 patients and selected 28 patients with sufficient pain relief by SCS (n=15) or PNS (n=13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 63 publications
0
12
0
3
Order By: Relevance
“…10 Furthermore, PNS decreases central sensitization and hyperalgesia by reducing excessive peripheral nociceptive activity in the spinal cord, inhibiting wide dynamic range of neurons in the dorsal horn, and decreasing Aβ fiber-induced activity in the medial lemniscal pathway in the brain. [11][12][13] Additionally, animal research has demonstrated that the analgesic effects of PNS may involve the serotonergic (5HT2, 5HT3), GABAergic, and glycinergic pathways. 14,15 Studies in the peripheral nervous system have demonstrated that PNS disrupts the transmission of nociceptive afferent fibers.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…10 Furthermore, PNS decreases central sensitization and hyperalgesia by reducing excessive peripheral nociceptive activity in the spinal cord, inhibiting wide dynamic range of neurons in the dorsal horn, and decreasing Aβ fiber-induced activity in the medial lemniscal pathway in the brain. [11][12][13] Additionally, animal research has demonstrated that the analgesic effects of PNS may involve the serotonergic (5HT2, 5HT3), GABAergic, and glycinergic pathways. 14,15 Studies in the peripheral nervous system have demonstrated that PNS disrupts the transmission of nociceptive afferent fibers.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Central mechanisms include inhibition of pain signals from inhibitory dorsal horn interneurons (Gate Control Theory), modulation of wide dynamic range (WDR) neurons in the dorsal horn, and reduction of neural impulses via the medial lemniscal pathway. By inhibiting WDR neurons in the dorsal horn, as well as reducing activity of A-β fibers in the medial lemniscal pathway, PNS may decrease the degree of central sensitization and hyperalgesia [ 16 , 17 ]. Furthermore, in the spinal cord, PNS may affect biochemical pathways, including serotonergic, GABAergic, and glycinergic pathways [ 18 ].…”
Section: Mechanism Of Peripheral Nerve Stimulationmentioning
confidence: 99%
“…Diverse neuromodulatory techniques have emerged in contemporary times, some of which remain largely within the domains of basic science, such as optogenetic modulation [ 2 , 3 ], while other methods have seen a massive clinical translation. Indeed, among today’s most well-established neuromodulatory treatments are transcranial magnetic stimulation (TMS) for depression [ 4 ], deep brain stimulation (DBS) of the basal ganglia to alleviate Parkinson’s disease [ 5 ], and spinal cord and peripheral nerve stimulation for chronic pain relief [ 6 ].…”
Section: Introductionmentioning
confidence: 99%